2013
DOI: 10.1152/ajpheart.00554.2013
|View full text |Cite
|
Sign up to set email alerts
|

Central control of cardiovascular function during sleep

Abstract: There is increasing evidence that cardiovascular control during sleep is relevant for cardiovascular risk. This evidence warrants increased experimental efforts to understand the physiological mechanisms of such control. This review summarizes current knowledge on autonomic features of sleep states [non-rapid-eye-movement sleep (NREMS) and rapid-eye-movement sleep (REMS)] and proposes some testable hypotheses concerning the underlying neural circuits. The physiological reduction of blood pressure (BP) during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 102 publications
3
78
0
1
Order By: Relevance
“…Thereafter, both ABP and HR eventually increased approximatively 15% of their respective values during NREM sleep in wild-type mice. 36 This is in line with the observations that ABP is approximately 10% lower during NREM sleep than during wakefulness in different species, 3,4 and that changes in HR during NREM sleep may contribute to determine those of ABP by modifying cardiac output. 6,7 Inspection of Fig.…”
Section: Changes In Abp and Hr Upon Awakening From Nrem Sleepsupporting
confidence: 81%
See 2 more Smart Citations
“…Thereafter, both ABP and HR eventually increased approximatively 15% of their respective values during NREM sleep in wild-type mice. 36 This is in line with the observations that ABP is approximately 10% lower during NREM sleep than during wakefulness in different species, 3,4 and that changes in HR during NREM sleep may contribute to determine those of ABP by modifying cardiac output. 6,7 Inspection of Fig.…”
Section: Changes In Abp and Hr Upon Awakening From Nrem Sleepsupporting
confidence: 81%
“…The values of ABP are approximately 10% lower during NREM sleep than during wakefulness, 3,4 which implies lower values of cardiac output and/or lower values of systemic vascular resistance (Fig. 1).…”
Section: Cardiovascular Control During Nrem Sleepmentioning
confidence: 98%
See 1 more Smart Citation
“…Increases in heart rate, lung volume, and eye muscle tension have been reported during or immediately following yawning [37]. SWS manifests decrease in blood pressure [38] and complex regulation of heart rate [39]. In electrophysiology, it has been demonstrated that the sleep-wake state can modulate the inspiratory motoneurons of respiration, while the tonic expiratory units are largely unaffected by the sleep-wake state [40].…”
Section: The Parallel Expiratory Driving Neurovascular Regulation In mentioning
confidence: 99%
“…Several studies have proposed that the correlation between motor activity level and cardiac activities (e.g., heart rate) are associated with closed-loop regulation of sympathetic nervous system during wakefulness as well as NREM sleep although two states are characterized by the different cardiac activity and sympathetic tone [6,7]. Interestingly, however, a study pointed out the possibility that the sympathetic regulation during eating behavior does not fit the cardiac-motor relationships typically seen during NREM sleep, quiet wakefulness, and waking behaviors [6].…”
Section: Introductionmentioning
confidence: 99%